2013
DOI: 10.2166/wst.2013.757
|View full text |Cite
|
Sign up to set email alerts
|

The impact of influent total ammonium nitrogen concentration on nitrite-oxidizing bacteria inhibition in moving bed biofilm reactor

Abstract: The application of nitrification-denitrification over nitrite (nitritation-denitritation) with municipal (i.e. diluted and cold (or low-temperature)) wastewater can substantially improve the energy balance of municipal wastewater treatment plants. For the accumulation of nitrite, it is crucial to inhibit nitrite-oxidizing bacteria (NOB) with simultaneous proliferation of ammonium-oxidizing bacteria (AOB). The present study describes the effect of the influent total ammonium nitrogen (TAN) concentration on AOB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 27 publications
2
8
0
1
Order By: Relevance
“…Moreover, there was always more NOB activity reduction in small granules than in large granules when exposed to the same FA concentration (Figure 11), once again suggesting that the large aerobic granules were more resistant than the small granules to FA inhibition. It is noteworthy that full nitrification granules in this study lost NOB activities for <25% at FA concentration between 1.0 and 5.0 mg N/L (Figures 10 and 11), revealing better FA resistance than NOB reported in the literature, which again is likely due to the irreversible FA resistance shown in Figure 11 and reported elsewhere (Kouba et al, 2014; Turk & Mavinic, 1989).…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…Moreover, there was always more NOB activity reduction in small granules than in large granules when exposed to the same FA concentration (Figure 11), once again suggesting that the large aerobic granules were more resistant than the small granules to FA inhibition. It is noteworthy that full nitrification granules in this study lost NOB activities for <25% at FA concentration between 1.0 and 5.0 mg N/L (Figures 10 and 11), revealing better FA resistance than NOB reported in the literature, which again is likely due to the irreversible FA resistance shown in Figure 11 and reported elsewhere (Kouba et al, 2014; Turk & Mavinic, 1989).…”
Section: Resultssupporting
confidence: 70%
“…The irreversible development of FA resistance is a plausible explanation for the observation. FA resistance was also concluded to be irreversible in several previous studies (Kouba et al, 2014; Turk & Mavinic, 1989), documenting the irreversible failure of nitrite accumulation after acclimation of NOB to FA in suspended culture of NOB (Turk & Mavinic, 1989) and nitrifying biofilms (Kouba et al, 2014). Figure 1a suggests that the partial nitrification granules with long‐term exposure to 0.77 ± 0.55 mg N/L FA have developed FA resistance that can even tolerate FA concentration higher than 10 mg N/L (Figure 11).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Considering this, it is possible that the higher aerobic fraction in the thinner biofilms could be a competitive advantage to the AOB, provided that the NOB in the system are Nitrospira rather than Nitrobacter. AOB and NOB are generally found in different layers of the biofilm, with NOB usually located deeper inside the biofilm than AOB [23,24]. It is possible that, in the thinner biofilms of this study, although the aerobically active biofilm layers are close to similar (as indicated by the ammonium removal), the space for NOBs at the very bottom of the biofilm layer, where DO is low, is limited.…”
Section: Nob and Aobmentioning
confidence: 77%
“…Specifically, Nitrosomonas spp.- and Nitrosospira spp.-related AOB were expected to dominate each metagenome typical of mainstream wastewater (Kim et al, 2011 ). Also, Nitrospira were expected to compete here as major NOB groups relative to Nitrobacter spp., which are more prevalent in sidestream systems (Blackburne et al, 2008 ; Kouba et al, 2014 ). The SG biofilm sample (SG BNR Biofilm) was analyzed in order to determine potential AMX presence and functionality, as aggregation in biofilms is typical of AMX-capable organisms due to secretion of extracellular polymeric substances (EPS; Tan et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%